Intraoperative Endoscopic Assessment of the Pouch and Anastomosis During Laparoscopic Roux-en-Y Gastric Bypass - (:unkn) unknown (SPRINGER, 2011)
As an advanced surgical procedure, laparoscopic Roux-en-Y gastric bypass (LRYGB) is associated with considerable morbidity, especially in the learning curve period. The aim of this study was to evaluate the role of endoscopy during LRYGB surgery in assessing the gastric pouch and anastomosis for air leak, bleeding, and structure at the beginning of a bariatric surgery program. Patients who underwent LRYGB for morbid obesity between May 2008 and May 2009 were included in this study. After the completion of the anastomosis, an endoscopic examination was carried out. The transection line and anastomosis site were examined for bleeding and patency and inspected for air leak under laparoscopic vision. Thirteen morbidly obese patients (mean body mass index, 48.0 +/- 6.8 kg/m(2)) were evaluated by endoscopic examination during the LRYGB operation. None of the cases had bleeding at the transection line or anastomosis site. In two patients, air leak test was positive and the anastomosis was reinforced with additional sutures. All the patients, including those with positive air leak test, were discharged from the hospital with no leak complications. After a mean follow-up of 9.1 +/- 5.5 months, except for the patient who underwent balloon dilatation, no other patient had anastomotic stricture. Intraoperative endoscopy is invaluable in the assessment of bleeding, anastomotic patency, and air leak during LRYGB, and it might be a helpful auxiliary tool to decrease morbidity during the learning curve period. Also, it helps solve intraoperative problems during the surgery so that postoperative complications might be prevented.
Keywords: BARIATRIC SURGERY; MORBID-OBESITY; GASTROJEJUNAL ANASTOMOSIS; MANAGEMENT; LEAKS; HEMORRHAGE; OUTCOMES; SERIES